2007
DOI: 10.1016/j.mehy.2006.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease may be a hyperimmune reaction of genetically susceptible children to variants of normal environmental flora

Abstract: Kawasaki disease (KD) is an acute febrile systemic vasculitis of unknown etiology that occurs predominantly in children <5 years of age. For the etiopathogenesis of KD, there is no agreement even as to whether KD is an infectious disease or an immune-mediated disease. The epidemiologic characteristics of KD, including the strict predilection of age in all ethnic groups and the gradually increased incidence after the KD emergence, suggest that KD is affected by the immune maturation in early childhood that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 73 publications
1
56
0
Order By: Relevance
“…Given the clear link to croplands/agricultural soils indicated by a variety of our results at a time and in a region where the ground is frozen throughout the high KD season, a whole range of new possibilities emerges regarding the nature of the KD etiological agent. Possibilities include environmental toxins linked to crops or to plant decay by-products (e.g., bacterial/fungal toxins), as well as a combination of the former with agricultural practices, atmospheric chemistry, and an idiosyncratic immune reaction in genetically susceptible children (28,29). The lack of an industrial signature in the inferred region and the lack of correlation with pollutant levels in the winds associated with increased KD activity argue against a chemical pollutant as the relevant causative agent.…”
Section: Discussionmentioning
confidence: 99%
“…Given the clear link to croplands/agricultural soils indicated by a variety of our results at a time and in a region where the ground is frozen throughout the high KD season, a whole range of new possibilities emerges regarding the nature of the KD etiological agent. Possibilities include environmental toxins linked to crops or to plant decay by-products (e.g., bacterial/fungal toxins), as well as a combination of the former with agricultural practices, atmospheric chemistry, and an idiosyncratic immune reaction in genetically susceptible children (28,29). The lack of an industrial signature in the inferred region and the lack of correlation with pollutant levels in the winds associated with increased KD activity argue against a chemical pollutant as the relevant causative agent.…”
Section: Discussionmentioning
confidence: 99%
“…KD is also self-resolving in 1-3 weeks and the most common age of acquiring KD is 6 months to 5 years when the susceptibility of the child to infections is also the highest [36]. Cases are rarely seen below 6 months of age which could be attributed to the passive transmission of maternal immunoglobulins providing protection to the child at an early age, which gradually decreases over the time [37]. Recently, Nagao et al also reported that KD has a similar mode of transmission to infections upon close contact with infected persons [38].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…It is thought that KD is an abnormal immunologic reaction to an infection in genetically susceptible individuals (Newburger and Fulton 2004;Lee et al 2007). There are several lines of evidence to support a genetic contribution to disease susceptibility and outcome.…”
Section: Introductionmentioning
confidence: 99%